Teaching and Learning Mathematics Using Facebook Group: NA - Rodulfo T. Aunzo (Journal La Edusci, 2021)
Almost every organization makes use of a Facebook group. They utilized it to debate themes and other problems concerning their own survival. Numerous mathematics instructors have already embraced its usefulness as a method of providing instructional materials to their pupils in the modern day. With these factors in mind, this research study on the use of Facebook groups in the teaching-learning process of mathematics was performed with the pioneer batch of ABM students at the University of San Carlos – Senior High School in Cebu City, Philippines. Through this amazing and updated communication medium, the kids learnt a new lesson. The statistical study revealed that the use of Facebook groups in the teaching-learning process of mathematics is beneficial. This is shown by the statistical equality of the experimental and control groups' post-test results. This demonstrates that the performance of students in the experimental and control groups is comparable. This is because the experimental groups did not participate in classroom discussions yet fared as well as the controls groups who did. Additional pertinent results from the research are provided in this article.